Specifics of Rail Transport Safety in Condition of the Czech Republic - null, null; Kavan, Štěpán (Kaunas University of Technology, 2018)
The paper deals with the issue of safety on railway communications in the Czech Republic. The primary goal is to analyze the specific features of safety on railway communications and its guarantee. The thesis identifies and analyzes the risks and the probable causes of emergencies. The secondary goal is focused on the safety of traffic regarding ČD Cargo, a. s. and suggests regulations to improve the current condition. The thesis studies the safety on railway communications, analyzes the railway sections that are necessary for the safe railway operation as well as the causes of emergencies and their consequences.
Specifika bezpečnosti železniční dopravy v podmínkách České republiky
Keywords: Emergency cases; security device; railway; mimořádné události; bezpečnostní zařízení; železnice